Participatory Digital Marketing and Branding Training for MSMEs Competitiveness - Sirajudin Alaksari; Anisah Anisah; Muhammad Rizzik (AKM, 2026)
The rapid development of digital technology requires Micro, Small, and Medium Enterprises (MSMEs) to adapt by implementing digital-based marketing strategies to enhance their competitiveness. However, many MSME actors still face limitations in utilizing digital marketing and strengthening product branding. This community service program aimed to improve the knowledge and practical skills of MSME actors through digital marketing and product branding training using a participatory practice-based approach. The program involved 28 MSME participants in Kampung Tujuh Village, Cermin Nan Gedang District, Sarolangun Regency. The methods included lectures, interactive discussions, hands-on practice, mentoring, and evaluation through observation sheets and practice assessment instruments. The evaluation indicators covered digital marketing understanding, product branding, target market identification, promotional content creation, and the use of digital media platforms. The results showed significant improvements in participants’ understanding and practical skills, with achievement scores increasing from initial conditions of 10%–20% to 70%–85% after the training. Participants also began implementing digital marketing strategies through social media platforms such as WhatsApp Business, Facebook, and Instagram. The participatory practice-based approach proved effective in improving both conceptual understanding and practical implementation skills among MSME actors. Therefore, this program can serve as an applicable and sustainable empowerment model for strengthening MSMEs competitiveness in the digital era.